The Effect of Products and Services on The Intention to Revisit Coastal Tourism Destinations in Madura Island - Wijayanti, Dian Eswin; Priyanto, Moh. Wahyudi; Qomariyah, Nor; Suprapti, Isdiana (Universitas Pendidikan Indonesia, 2024)
ABSTRACTTourism is a strategic sector that has a multiplier effect on other sectors, including reducing poverty and increasing the income of residents around the destination. This is evidenced by the increase in the country's foreign exchange. Its potential must be maximized by making destinations friendly and comfortable for tourists, to create satisfaction and good experiences that lead to revisit. There is a strong hypothesis about the role of tourist destination products and services in increasing tourist satisfaction. Therefore, this research aims to explore the effect of destination products and services on tourists' intention to revisit. Using convenience sampling techniques, 89 tourists from Batu Kerbuy Beach, Pamekasan and Telaga Biru Beach, Bangkalan were interviewed. We found that tourists were dissatisfied with 4 types of products and services, namely service; cleanliness of service employees; courtesy of service employees; and availability of public transportation. Meanwhile, perception of accommodation and food and drink quality varied (there was no dominant perception). This needs to be resolved because ordered probit regression analysis shows that products and services (facilities) were found to have a positive effect on tourists' intention to revisit. In addition, age, income, fulfillment of needs, and assessment of destinations that are worth it have a positive effect on tourist intentions. This study can be a scientific consideration for local governments to make policies. ABSTRAKPariwisata adalah sektor strategis yang memberikan multiplier efek pada sektor lainnya, diantaranya mengurangi kemiskinan dan meningkatkan pendapatan penduduk sekitar destinasi. Hal itu dibuktikan oleh peningkatan devisa negara. Potensinya harus dimaksimalkan dengan cara membuat destinasi yang ramah dan nyaman bagi wisatawan, supaya menciptakan kepuasan dan pengalaman yang baik sehingga berujung pada kunjungan kembali. Ada hipotesis yang kuat terhadap peran produk dan jasa destinasi wisata terhadap peningkatan kepuasan wisatawan. Oleh karena itu, penelitian ini bertujuan untuk mengeksplorasi efek produk dan jasa destinasi terhadap niat wisatawan untuk berkunjung kembali. Wawancara dengan teknik convenience sampling dilakukan kepada 89 wisatawan Pantai Batu Kerbuy, Pamekasan dan Pantai Telaga Biru, dan Bangkalan. Kami menemukan bahwa wisatawan tidak puas terhadap 4 jenis produk dan jasa, yakni pelayanan; kerapian petugas pelayanan; kesopanan petugas pelayanan; dan transportasi umum. Sedangkan persepsi terhadap akomodasi dan kualitas makanan dan minuman bervariasi (tidak ada persepsi yang dominan). Hal ini perlu diselesaikan karena analisis regresi ordered probit menunjukkan bahwa produk dan jasa (fasilitas) ditemukan memiliki efek positif terhadap niat wisatawan untuk berkunjung kembali. Selain itu, usia, pendapatan, pemenuhan kebutuhan, dan penilaian destinasi yang worth it ditemukan memiliki efek positif terhadap niat wisatawan. studi ini bisa menjadi pertimbangan ilmiah bagi pemerintah daerah untuk membuat kebijakan.